The Strength of Proof of Telephone Tapping As Electronic Evidence in Revealing Corruption Cases - Aga Wigana Wigana; Maryanto Maryanto (Jurnal Daulat Hukum, 2020)
This study try to answer the question: 1) Why is the wiretapping in investigations of corruption, 2) How wiretapping conducted in the investigations conducted by investigators of corruption, connected with the legal provisions in force of Indonesia 3) In the circumstances of how the interception of the telephone as electronic evidence can be accepted as evidence legitimate in the proof of corruption cases. This research using normative juridical approach, with specification of descriptive analytical research. The data used in this research is secondary data obtained from books and scientific papers as well as data tertiary derived from articles and Internet news, dictionaries legal and material outside the legal field which is then analyzed qualitatively using equity theory, the theory of punishment, the theory of legal certainty and the theory of legal protection.Results of the discussion concluded that Wiretapping (Interference) by phone is required to disclose the existence of corruption are the modus increasingly diverse, particularly for evidence of bribes or gratuities are not reported, the constraints are rules about wiretapping not been clearly defined, especially for police investigators and investigators prosecutors, therefore it needs to be regulated in Law on wiretapping which contains a complete 'authority, mechanism or procedure for tapping activities and results, in addition to tapping activities undertaken should continue to promote the values of human rights of citizens, in addition to telephone tapping can be accepted as valid evidence in trial of corruption cases, if the principles of retrieval and storage of electronic data (chain of custody) maintained to ensure its validity as electronic evidence in proving the case in court.Keywords: Strength of Evidence; Tapping; Electronic Evidence; Corruption.